2022
DOI: 10.3390/diagnostics12071563
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors Mimicking Gynecologic Disease: Clinicopathological Analysis of 20 Cases

Abstract: Diagnosis of pelvic gastrointestinal stromal tumors (GISTs) can be challenging because of their nonspecific presentation and similarity to gynecological neoplasms. In this series, we describe the clinicopathological features of 20 GIST cases: 18 patients presented with pelvic mass and/or abdominal pain concerning gynecological disease; 2 patients presented with a posterior rectovaginal mass or an anorectal mass. Total abdominal hysterectomy and/or salpingo-oophorectomy (unilateral or bilateral) were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…13 There have been rare reports of GIST metastasizing to the ovary. [14][15][16][17] From our study, we found a case of metastasis of GIST to the left ovary. This was in a 54-year-old woman.…”
Section: Discussionmentioning
confidence: 66%
“…13 There have been rare reports of GIST metastasizing to the ovary. [14][15][16][17] From our study, we found a case of metastasis of GIST to the left ovary. This was in a 54-year-old woman.…”
Section: Discussionmentioning
confidence: 66%
“…Another study showed that 56.2% (9/16) of incidentally found GISTs in gynecological surgery were located in the stomach wall, cecum, omentum and mesentery [9]. These cases also presented with GI symptoms, such as abdominal pain [7]. This case is unique as the patient only complained vaginal bleeding without any GI symptoms.…”
Section: Discussionmentioning
confidence: 84%
“…The majority of the EGISTs cases in the pelvic involved the GI tracts, as shown in a 10-year retrospect pelvic GISTs study where 65% (13/20) cases originated from small bowel, 15% (3/20) originated from rectum, 15% (3/20) originated from stomach and 1 had unavailable primary site information [7]. Another study showed that 56.2% (9/16) of incidentally found GISTs in gynecological surgery were located in the stomach wall, cecum, omentum and mesentery [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For this reason, high-grade endometrial stromal sarcoma entered the differential diagnosis despite focal/nondiffuse positivity of cyclin D1 and negative BCOR staining. Although CD117 was diffusely positive, a gastrointestinal stromal tumor was not included in the differential diagnosis because of a negative DOG-1 immunostaining and location 16 . The mechanism which drives CD117 expression is unclear since c-KIT mutation or amplification was not detected in this tumor.…”
Section: Discussionmentioning
confidence: 99%